The Normativity of Limited Company Under Job Creation Law Regime: A Critical Legal Studies Perspective - Sekarasih, Setijati; Budiono, Abdul Rachmad; Sukarmi, Sukarmi; Santoso, Budi (Batulis Civil Law Review, 2023)
Introduction: The concept of a limited liability company based on Law Number 11 of 2020 concerning Job Creation (UU Cipta Kerja) through Government Regulation in Lieu of Law Number 2022 concerning Job Creation (Perppu Cipta Kerja) after being declared conditionally unconstitutional by the Constitutional Court, has now found its foundation again.Purposes of the Research:  This article examines the normativity of limited liability companies after the Perppu Cipta Kerja in two focuses. First, it relates to the legal ratio for the establishment of an individual company, and second, the normativity of an individual company from the perspective of Critical Legal Studies.Methods of the Research: This paper uses a normative juridical approachResults of the Research: Based on the type of normative research supported by conceptual, statutory, and philosophical approaches, this article concludes two: First, the legal ratio for the establishment of individual companies in the Perppu Cipgta Kerja is the government's great desire to provide convenience for MSEs in doing business and creating jobs. Second, based on the analysis of trashing, deconstruction, and genealogy, individual companies in the Perppu Cipta Kerja are still full of liberal individualism with a capitalist economic system style.